High resolution Cerenkov light imaging of induced positron distribution in proton therapy. Issue 11 (27th October 2014) - Yamamoto, Seiichi; Toshito, Toshiyuki; Fujii, Kento; Morishita, Yuki; Okumura, Satoshi; Komori, Masataka
Abstract : Purpose: In proton therapy, imaging of the positron distribution produced by fragmentation during or soon after proton irradiation is a useful method to monitor the proton range. Although positron emission tomography (PET) is typically used for this imaging, its spatial resolution is limited. Cerenkov light imaging is a new molecular imaging technology that detects the visible photons that are produced from high‐speed electrons using a high sensitivity optical camera. Because its inherent spatial resolution is much higher than PET, the authors can measure more precise information of the proton‐induced positron distribution with Cerenkov light imaging technology. For this purpose, they conducted Cerenkov light imaging of induced positron distribution in proton therapy. Methods: First, the authors evaluated the spatial resolution of our Cerenkov light imaging system with a 22 Na point source for the actual imaging setup. Then the transparent acrylic phantoms (100 × 100 × 100 mm 3 ) were irradiated with two different proton energies using a spot scanning proton therapy system. Cerenkov light imaging of each phantom was conducted using a high sensitivity electron multiplied charge coupled device (EM‐CCD) camera. Results: The Cerenkov light's spatial resolution for the setup was 0.76 ± 0.6 mm FWHM. They obtained high resolution Cerenkov light images of the positron distributions in the phantoms for two different proton energies and made fused images of the reference images and the Cerenkov light images. The depths of the positron distribution in the phantoms from the Cerenkov light images were almost identical to the simulation results. The decay curves derived from the region‐of‐interests (ROIs) set on the Cerenkov light images revealed that Cerenkov light images can be used for estimating the half‐life of the radionuclide components of positrons. Conclusions: High resolution Cerenkov light imaging of proton‐induced positron distribution was possible. The authors conclude that Cerenkov light imaging of proton‐induced positron is promising for proton therapy.